Perancangan Sistem Informasi Pengelolaan Zakat Dan Infaq Menggunakan Metode Personal Extreme Programming Berbasis Web Di Musholla Al-Muhajirin - Allan Firmansyah; Bambang Wisnu Widagdo (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Zakat is a worship that concerns property that has a social function. Every Muslim is obliged to pay zakat. As one of the intermediaries, Musholla Al-Muhajirin can collect data and distribute it to those in need. In implementing this zakat management system, there are several things that become a problem, namely the form of zakat management reports that are currently still in handwriting which can complicate the process of searching data, the possibility of missing data and being vulnerable to damage. With the reasons above, the author tries to provide a solution to solving the problem by creating a zakat management system that will record incoming zakat and then make it systematic and computerized using the personal extreme programming method at Al-Muhajirin Mosque. In this writing, the stages of work will also be explained, starting from the process of analysis, planning, construction using a web-based application and MySQL as its database, to the implementation stage with engineering notation and an object-oriented UML (Unified Modeling Language) approach. The result of this final project is a web-based zakat and infaq management information system that makes it easy for amil to manage zakat and for muzaki to pay zakat. The benefit of this system is that it will create transparency of zakat management data. This system will later become a reference for DKM Musholla Al-Muhajirin in the process of managing zakat and infaq and become the next system development.